2017
DOI: 10.1177/0954410017704217
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design and experiment of propellers for high altitude airship

Abstract: The multi-objective optimization design method and experimental validation of the propeller for high altitude airships are presented in this paper. The method of predicting the propeller's aerodynamic characteristics is based on the vortex theory. The non-dominated sorting genetic algorithm II is introduced and applied to solve the optimization problem. Then the optimization model which aims to design an efficient and lightweight propeller for high altitude airships is established based on the conditions of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
0
12
0
6
Order By: Relevance
“…Furthermore, reliable operation of the designed propeller in certain, specified, even unconventional working regimes also becomes attainable. Some examples of the research of high altitude propellers can be found in [9][10][11].…”
Section: Propeller Design and Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, reliable operation of the designed propeller in certain, specified, even unconventional working regimes also becomes attainable. Some examples of the research of high altitude propellers can be found in [9][10][11].…”
Section: Propeller Design and Optimizationmentioning
confidence: 99%
“…The work presented in [9] uses a single airfoil (constant function) and 4th order distributions of both chord and pitch. Similarly, [10] employs four predefined airfoils together with 3 rd order functions for c(r) and θ(r). This research describes a possible approach to the optimization of all three relevant blade features without the use of any constant or predefined values.…”
Section: Computational Bemt Modelmentioning
confidence: 99%
“…Una vez establecido el modelo, las siguientes dos cuestiones relevantes son qué es lo que se va a optimizar del diseño, y qué método se va a utilizar para conseguir esta optimización. Debido al aumento de la disponibilidad de los recursos computacionales, en losúltimos años han surgido diversos trabajos en los que la optimización se lleva a cabo usando machine learning e inteligencia artificial (e.g Jiao et al [59])). Sin embargo, ese tipo de métodos tienen como inconveniente la dificultad en hallar significado físico en la solución.…”
Section: Estado De Las Tecnologíasunclassified
“…Jiao et al [59] usó como método de optimización un algoritmo genético. Haciendo una estimación de la masa de la hélice, aplicó como función de coste una combinación entre este peso y la eficiencia aerodinámica.…”
Section: Estado De Las Tecnologíasunclassified
See 1 more Smart Citation